Analysis of Damage Value on the Babat – Jombang District Boundary Road Segment (Link.105) Using the Provincial/District Road Management System (PKRMS) Application: Analisis Nilai Kerusakan Ruas Jalan Babat – Batas Kabupaten Jombang (Link.105) Menggunakan Aplikasi Provincial/Kabupaten Road Management System (PKRMS) - Wibisono, R. Endro; Elvira, Anggie Dea (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2025)
Pavement damage can occur due to excessive traffic loads, extreme weather and so on which have an impact on hampering surrounding activities so that road users feel less safe and less comfortable. Road damage also occurs on the Babat - Bts Jombang Regency road section. To keep the road condition in good performance, it is necessary to evaluate it with a road condition survey. In processing the data from the road condition survey, UPT Pengelolaan Jalan dan Jembatan Surabaya uses the Provincial / Regency Road Management System (PKRMS) application as a database for planning purposes that holds condition data, inventory, project data, historical data, and maps. The result of this PKRMS is statistical report data on road damage conditions with the Treatment Trigger Index (TTI) calculation method. From the observation locations reviewed, the results show that the Babat - Bts Jombang Regency road section which has a section length of 30.785 kilometers and a road width of 7 meters is in a stable condition with a percentage of 83.81% or along 25.88 kilometers and 16.19% or 5 kilometers is in a less stable condition.